Extending storage potential of de‐hulled fresh pistachios in passive‐modified atmosphere. (11th February 2019) - Sheikhi, Abdollatif; Mirdehghan, Seyed H; Ferguson, Louise
Abstract: Background: The effects of passive modified‐atmosphere packaging (passive‐MAP) on the postharvest quality of de‐hulled fresh pistachios ( Pistacia vera L. cv. Kerman) stored at cold temperature (0 ± 0.5 °C) and 90 ± 1% relative humidity was investigated with fruits under ambient air condition as the control treatment. The fruit quality parameters measured included kernel firmness, color values ( L *, a *, b *, h °, and C * ), weight loss, fungal decay and marketability, ethylene production, respiration rate, and sensory characteristics at 0, 30, 60, and 105 days of storage. The carbon dioxide (CO2 ) and oxygen (O2 ) concentrations in the package headspace were monitored during storage. RESULTS: A modified atmosphere of 0.95–3.35% O2 and 23.17–29.82% CO2 was achieved in the passive‐MAP treatment. Fruit respiration rates increased significantly relative to controls throughout storage ( P  ≤ 0.01). However, storage had no significant effect on ethylene production rates. Additionally, passive‐MAP‐stored fruits maintained firmness, shell lightness, kernel color, and sensory quality with minimum weight loss and fungal decay, compared with the control. CONCLUSION: These results demonstrate storage life of fresh pistachios in passive‐MAP can be extended up to 105 days, compared with 30 days in ambient conditions. © 2019 Society of Chemical Industry